An Occupant-Centric Theory of Building Control Systems and Their User Interfaces - Ardeshir Mahdavi; Helene Teufl; Christiane Berger (Energies, 2021)
This paper presents an occupant-centric theory of buildings’ indoor-environmental control systems and their user interfaces. Buildings typically can have multiple devices and systems to maintain indoor-environmental conditions within certain ranges in order to meet occupants’ health and comfort requirements. Therefore, it is important to understand what those ranges are exactly, who defines them, and for whom. Health and comfort sciences offer some broad directions concerning desirable indoor conditions. These are typically formulated in various codes, standards, and guidelines in terms of target values or the set points of control variables. However, preferable conditions may differ at different times and for different individuals. Another question concerns the agency responsible for maintaining the preferred conditions. In some settings, conditions may be centrally controlled via the buildings’ automation systems, whereas in other settings, occupants might have the possibility to control their immediate surroundings. Given these qualifications, the objective of the present inquiry can be stated more precisely. We outline a human-ecologically inspired theory pertaining to the occupants’ perception of and interaction with a building’s indoor-environmental control systems and their user interfaces. Specifically, we explore the operationalization potential of the proposed theory as a compact assessment protocol for the evaluation of buildings’ responsiveness to occupants’ preferences. Initial experiences with the derivative protocol are promising. Nonetheless, in order to be fully applicable in practice, certain challenges must be addressed. These specifically include the need for more robust procedures toward the translation of occupants’ subjective judgments into quantitative evaluation scales.